Production of chitosan-based biodegradable active films using bio-waste enriched with polyphenol propolis extract envisaging food packaging applications - De Carli, Cristiane (2022)
Developing biodegradable active films has been a promising green approach to overcoming global concerns over the environmental pollution and human health caused by plastic utilization. This study aimed to develop active films based on chitosan (CS), produced from waste crayfish (Procambarus clarkii) shells enriched with bioactive extract (5–20%) of propolis (PS) and to characterize its properties, envisaging food packaging applications. The chromatographic profile of PS extract confirmed its richness, with 41 phenolic compounds. With increasing extract addition to the chitosan, the thickness of the films increased from 61.7 to 71.7 μm, causing a reduction in the light transmission rate, along with a greenish colour shift. The interactions between PS extract and CS was confirmed by infrared spectroscopy, at the same time that the microstructural integrity of the films was checked on the scanning electron microscopy micrographs. The findings also showed that addition of PS enhanced the films thermal stability and mechanical properties e.g., tensile modulus, yield strength, and stress at break. Besides, it improved the antioxidant and antimicrobial activities. Overall, CS-based composite films seem a promising green alternative to petroleum-based synthetic plastics allowing to extend the shelf life of food products due to their eco-friendly nature.